Bier spots - Ahu Yorulmaz; Seray Kulcu Cakmak; Esra Ar?; Ferda Artuz (Our Dermatology Online, 2015)
Also called as physiologic anemic macules, Bier spots are small, hypopigmented irregularly shaped macules against a background of diffuse erythema, which creates an appearance of speckled vascular mottling of the skin. Bier spots most commonly appear on distal portions of the limbs though there are case reports describing diffuse involvement, which also affect trunk and mucous membranes of the patient. Although the exact pathophysiological mechanisms underlying Bier spots still need to be elucidated, Bier spots have been suggested to be a vascular anomaly caused by vasoconstriction of small vessels. In addition, several diseases have been proposed to be associated with Bier spots, including scleroderma renal crisis, cryoglobulinemia, Peutz-Jeghers syndrome, alopecia areata and hypoplasia of the aorta, although it has not been shown whether these associations are casual or coincidental. The clinical presentation of Bier spots is quite typical. These tiny whitish macules easily become prominent when the affected limb is placed in a dependent position and fade away when the limb is raised. Here we report a case of Bier spots in a 32-year-old male patient with characteristical clinical manifestations.